Inovasi Media Pembelajaran Interaktif Menggunakan WPS Office pada Pembelajaran Statistika - Kadir, Abd. Wahid; Machmud, Tedy; Damayanti, Taulia (Universitas Negeri Gorontalo, 2025)
Innovation in interactive learning media is essential to improve the effectiveness of statistics instruction at the junior high school level. This study aimed to develop interactive learning media based on WPS Office to support Statistics learning for eighth-grade junior high school students. The research employed the ADDIE development model, encompassing five stages: Analysis, Design, Development, Implementation, and Evaluation. The media was designed using WPS Presentation and Canva, and then converted into an Android application using Website 2 APK Builder Pro. Validation was conducted by media and subject experts; practicality was assessed by teachers and students. Validation results showed very high feasibility, with an average score of 94.32% from media experts and 95.37% from subject experts. Practicality testing yielded scores of 95.33% from teachers and 93.42% from students, indicating that the media is highly practical and engaging. The developed media is valid, practical, and relevant for supporting contextual and interactive digital learning. It has potential to improve students' conceptual understanding of statistics and their digital literacy.